The paradigm challenged: a new analysis of the origin of "diakonia" - Latvus, Kari (Studia theologica, 2008)
The classical paradigm saw the apostolic and biblical age as a special moment for the diaconal ministry. The important role of the diaconal ministry continued for just a few centuries and finally withered. According to this study, the traditional outline is not historically true, or at least we need new evidence in order to argue for the biblical origin of a social-caritative diaconal ministry. Following the interpretation of New Testament texts by Luther and Calvin, the 19th century diaconia movement projected its own life setting into the ancient texts. Thus the return to the biblical ministry of diaconia actually turned out to be a reinterpretation of biblical and early church writings. The ministry of diakonos in the early church was not invented by the modern movement, but it gave a totally new meaning to the ancient Greek concept and also launched a new way to use diakonia-derivative vocabulary.